The impact of estradiol on serotonin, glutamate, and dopamine systems - Bendis, Peyton Christine; Zimmerman, Sydney; Onisiforou, Anna; Zanos, Panos; Georgiou, Polymnia (Frontiers in Neuroscience, 2024)
Estradiol, the most potent and prevalent member of the estrogen class of steroid hormones and is expressed in both sexes. Functioning as a neuroactive steroid, it plays a crucial role in modulating neurotransmitter systems affecting neuronal circuits and brain functions including learning and memory, reward and sexual behaviors. These neurotransmitter systems encompass the serotonergic, dopaminergic, and glutamatergic signaling pathways. Consequently, this review examines the pivotal role of estradiol and its receptors in the regulation of these neurotransmitter systems in the brain. Through a comprehensive analysis of current literature, we investigate the multifaceted effects of estradiol on key neurotransmitter signaling systems, namely serotonin, dopamine, and glutamate. Findings from rodent models illuminate the impact of hormone manipulations, such as gonadectomy, on the regulation of neuronal brain circuits, providing valuable insights into the connection between hormonal fluctuations and neurotransmitter regulation. Estradiol exerts its effects by binding to three estrogen receptors: estrogen receptor alpha (ERα), estrogen receptor beta (ERβ), and G protein-coupled receptor (GPER). Thus, this review explores the promising outcomes observed with estradiol and estrogen receptor agonists administration in both gonadectomized and/or genetically knockout rodents, suggesting potential therapeutic avenues. Despite limited human studies on this topic, the findings underscore the significance of translational research in bridging the gap between preclinical findings and clinical applications. This approach offers valuable insights into the complex relationship between estradiol and neurotransmitter systems. The integration of evidence from neurotransmitter systems and receptor-specific effects not only enhances our understanding of the neurobiological basis of physiological brain functioning but also provides a comprehensive framework for the understanding of possible pathophysiological mechanisms resulting to disease states. By unraveling the complexities of estradiol’s impact on neurotransmitter regulation, this review contributes to advancing the field and lays the groundwork for future research aimed at refining understanding of the relationship between estradiol and neuronal circuits as well as their involvement in brain disorders.